Pressure build-up analysis in the flow regimes of the CO2 sequestration problem - Sarris, Ernestos; Gravanis, Elias; Papaloizou, Loizos (My University, 2020)
In this work we analyse theoretically and numerically the pressure build-up on the cap rock of a saline aquifer during CO2 injection in all flow regimes. Flow regimes are specific regions of the parameter space representing the mathematical spread of the plume. The parameter space is defined in terms of the CO2-to-brine relative mobility λ and the buoyancy parameter Γ. In addition to the known asymptotic self-similar solutions for low buoyancy regimes, we introduce two novel ones for the high buoyancy regimes via power series solutions. Explicit results for the peak pressure value on the cap, which arises in the vicinity of the well, are derived and discussed for all flow regimes. The analytical results derived are then applied for cap integrity considerations in six test cases of CO2 geological storage from the PCOR partnership, most of which correspond to high buoyancy conditions. The validity of the self-similar solutions which are late time asymptotics, is verified with CFD numerical simulations with a commercial software. The comparison between the self-similar solutions and CFD for the pressure estimations are in excellent agreement and the self-similar solutions are valid for typical injection durations even for early times.
Keywords: Aquifers; Buoyancy; Carbon dioxide